Telephone outreach by community workers to improve uptake of NHS Health Checks in more deprived localities and minority ethnic groups: a qualitative investigation of implementation. (12th June 2019) - Stone, T J; Brangan, E; Chappell, A; Harrison, V; Horwood, J
Abstract: Background: NHS Health Checks is a national cardiovascular risk assessment and management programme in England. To improve equity of uptake in more deprived, and Black, Asian and minority ethnic (BAME) communities, a novel telephone outreach intervention was developed. The outreach call included an invitation to an NHS Health Check appointment, lifestyle questions, and signposting to lifestyle services. We examined the experiences of staff delivering the intervention. Methods: Thematic analysis of semi-structured interviews with 10 community Telephone Outreach Workers (TOWs) making outreach calls, and 5 Primary Care Practice (PCP) staff they liaised with. Normalization Process Theory was used to examine intervention implementation. Results: Telephone outreach was perceived as effective in engaging patients in NHS Health Checks and could reduce related administration burdens on PCPs. Successful implementation was dependent on support from participating PCPs, and tensions between the intervention and other PCP priorities were identified. Some PCP staff lacked clarity regarding the intervention aim and this could reduce the potential to capitalize on TOWs' specialist skills. Conclusions: To maximize the potential of telephone outreach to impact equity, purposeful recruitment and training of TOWs is vital, along with support and integration of TOWs, and the telephone outreach intervention, in participating PCPs.